Concurrent ROS1 gene rearrangement and KRAS mutation in lung adenocarcinoma: A case report and literature review. Issue 1 (3rd October 2017) - Zhu, You‐cai; Lin, Xue‐ping; Li, Xiao‐feng; Wu, Li‐xin; Chen, Hua‐fei; Wang, Wen‐xian; Xu, Chun‐wei; Shen, Jian‐fa; Wei, Jian‐guo; Du, Kai‐qi
Abstract : Lung adenocarcinomas with gene rearrangement in the receptor tyrosine kinase ROS1 have emerged as a rare molecular subtype. Although these lung adenocarcinomas respond to ROS1 tyrosine kinase inhibitors, many patients ultimately acquire resistance. ROS1 gene rearrangement is generally mutually exclusive with other driver genomic alterations, such as those in EGFR, KRAS, or ALK, thus multiple genomic alterations are extremely rare. Herein, we report a case of a 42‐year‐old man diagnosed with lung adenocarcinoma positive for a SDC4‐ROS1 fusion, who was treated with crizotinib followed by three cycles of chemotherapy. A biopsy acquired after disease progression revealed the original SDC4‐ROS1 fusion along with a KRAS point mutation (p.G12D).We reviewed the related literature to determine the frequency of gene mutations in non‐small cell lung cancer patients. A better understanding of the molecular biology of non‐small cell lung cancer with multiple driver genomic aberrations will assist in determining optimal treatment.